HI-Shaped Antenna for Non-Invasive Diabetes Measurement and Monitor Fluctuating Diabetes - Kirubakaran, S.J.; Bennet., M; Shanker, N. R. (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2023)
The HI antenna senses the human pancreas dielectric radiation for diabetic measurement. Existing passive sensor antennas sense the dielectric radiation from the pancreas region at frequencies of 402.5 MHz and 2.4 GHz for a relative permittivity of 61.2155 and 57.201, respectively. The proposed antenna senses the dielectric properties of diabetic-affected pancreas, such as low and high-fat diabetic pancreas, in the frequency range between 1.5 GHz and 3 GHz. The relative permittivity of the diabetic pancreas is in the range of 48.235 to 65.508. The proposed antenna can sense the diabetic range between 70 mg/dl and 475 mg/dl based on a change in dB level, whereas the existing diabetic sensing antenna measures the diabetic level based on resonance frequency. The resonance-frequency-based diabetic measurement shows inaccurate results. The HI antenna senses pancreas radiation effectively because of the shape and size of its slot, which covers the pancreas region of the human body without generating noise due to the crumbling effect during pancreas dielectric radiation acquisition. The proposed HI-shaped antenna is mounted in different parts of the human body, such as the hand, finger, stomach, and pancreas, for measuring fluctuating diabetes. Based on the experimental results of the proposed HI-shaped antenna, the pancreas is in an optimal location among the various parts of the body. The proposed HI-shaped antenna-based dielectric signal statical values were correlated with diabetic laboratory values for prediction of the diabetic value. The proposed antenna measures the fluctuation in diabetes with 85% accuracy